Recent Advances in Understanding Immunity Against Brucellosis: Application for Vaccine Development - Costa Oliveira, Sergio (2010)
Brucellosis is an important zoonotic disease of nearly worldwide distribution. This pathogen causes abortion in cattle and undulant fever, arthritis, endocarditis and meningitis in human. The immune response against B. abortus involves innate and adaptive immunity involving antigen-presenting cells, NK cells and CD4+ and CD8+ T cells. IFN- is a crucial immune component that results from Brucella recognition by host immune receptors such as Toll-like receptors (TLRs) that lead to IL-12 production. Although great efforts to elucidate immunity against Brucella have been employed, the subset of cells and factors involved in host immune response remains not completely understood. Our group and others have been working in an attempt to understand the mechanisms involved in innate responses to Brucella. Understanding the requirements for immune protection can help the design of alternative vaccines that would avoid the drawbacks of currently available vaccines to Brucella. This review discusses recent studies in host immunity to Brucella and new approaches for vaccine development.